Crise no underground londrino: uma análise do Led Zeppelin IV - Arruda, Ricardo Sinigaglia [UNIFESP] (2019)
On November 8th 1971, the English rock band Led Zeppelin released their fourth, untitled, album. Having 22 million copies sold, its success was seen by the record label Atlantic Records as a professional suicide. On this album, the tracks are referring to the 60s rock’s cultural form, when London’s underground offered possibilities of producing musical experiments. However, the album also has transformations, typical of the beginning of the 70s, when rock music was tied to subgenres, in order to be assimilated by marketing strategies and sold in each one of the segmented markets. This situation was due to a London underground scene crisis and this research aims to investigate how much of this crisis can be heard in Led Zeppelin IV and how the band reacted to the new subgenres.